Recent Progress in Self-sensing Probe Technology in Atomic Force Microscope - Xu, Ke; Ji, Chenghao; Wei, Fanan; Zhai, Zhushan (Current Nanoscience, 2021)
The imaging speed of atomic force microscope (AFM) is limited by the cantilever mechanical bandwidth, which can be increased by reducing the size of the cantilever. However, the ordinary laser reflection method cannot measure the deflection of a small cantilever. Moreover, some samples are sensitive to light detection and not suitable for the laser reflection method. Therefore, the self-induction probe technology was developed to solve this problem. This article reviews the latest AFM self-induction probe technology and introduces three types of self-induction probes. Firstly, it is introduced that the current self-sensing probes can be divided into piezoresistive type, piezoelectric type and tuning fork type according to the working mechanisms and preparation materials. Then, the latest materials and structures of various self-sensing probe technologies are introduced to improve imaging performance and their applications in various fields. Moreover, compared with traditional laser reflection methods, the self-sensing probe technologies have a simpler structure, take up less space and can be integrated in a large cantilever array and adopted for imaging of photosensitive products. Finally, some prospects of the novel imaging and sample characterization techniques and new applications of atomic force microscopy are also discussed.
Keywords: Atomic force microscope